Peran Kepala Sekolah Sebagai Educative Leader Terhadap Optimalisasi Mutu Pendidikan - Nurdin; Risma Yunita; Dwi Bhakti Oktavianto; Fadillah, Firda Fahriana; Putri Intan Altafunnisa (PT. Intelek Cendikiawan Nusantara, 2024)
Abstract The various problems that arise in the world of education are basically caused by various factors that surround it. Improvements at the top level, middle level and lower level are needed to produce equitable education quality standards. At the education unit or school level, the presence of a leader (headmaster) is needed to improve the organizational climate and synchronize with policy makers at the central level. This means that school headmasters have a stake in the process of improving the quality of education. In this regard, this study attempts to further examine the role of school headmasters in optimizing the quality of education. Matters relating to the ideal aspects of the headmaster's position are the main discussion in this study. These aspects will be used to answer questions about efforts to optimize the quality of education in schools. The method used in this research is the library research method. The results of this study indicate that, 1) as an educative leader, the headmaster should ideally have certain competencies such as a mover, determinant, mediator, and motivator; 2) the competencies possessed by the headmaster as an educative leader are closely related to efforts to optimize the quality of education. If the headmaster is able to optimize his role, the quality of education which includes the quality of educators, curriculum implementation, and students will reach its ideal point.